Evaluation of starches from selected yellow and white flesh cassava roots for noodles production - Akinde, H.A. (Federal University of Agriculture, Abeokuta, 2020)
Cassava starch has been prospected in many food products manufacture. However, its suitability for making starch noodle has not been reported. Hence, this study was conducted to determine cassava starch‘s suitability in starch noodles production. The study was based on a completely randomized design with cassava variety as the main source of variation. The physicochemical properties [paste clarity (PCL), gel strength (GS), retrogradation], amylose content (AC), thermal properties [onset temperature, To), (peak temperature Tp), (final temperature Tf), and enthalpy of reaction ΔH], functional properties [swelling power (SP), solubility, and least gelation concentration LGC], and pasting properties [peak viscosity (PV), final viscosity (FV), setback, peak time (PKT), pasting temperature (PST)] of starches from eight cassava varieties (TMS 01/1368, TMS 01/1412, TMS 01/1206, TMS 01/1371, TMS 30572, TME 419, TMS 96/1632, and TMS 98/0581) were first determined using standard laboratory procedures. Noodles were thereafter produced from the starches using hot extrusion method. The colour (L*, a*, and b*), textural properties (chewiness, hardness, and gumminess), affective sensory properties (colour, transparency, glossiness and overall acceptability) as well as the descriptive sensory attributes (brownness, whiteness, transparency, brittleness, flexibility, and glossiness) of uncooked and cooked cassava starch noodles were compared with a commercial starch noodles as reference sample. Data were subjected to descriptive and inferential statistics, using Statistical Package for the Social Sciences (SPSS, version 21). The range of PCL, GS, retrogradation, and AC of cassava starch samples was 71.38-85.23, 14.88-27.94, 31.67-49.07, and 16.0-28.8%, respectively. To, Tp, and Tf, were in the range 43.12-57.46, 90.62-130.57, and 127.62-138.1 °C, respectively, while ΔH ranged from -335.78-73.77 J/g. SP at 60, 70, 80, 90, and 100 °C ranged from 2.88-4.38, 7.36-10.91, 5.99-9.80, 4.19-11.04, and 4.30-7.63 °C, respectively. Solubility index at 60, 70, 80, 90, and 100 °C ranged from 1.0-2.33, 1.33-20.33, 1.0-11.33,7.33-48.33, and 16.3-40.67%, respectively. LGC ranged from 2.00-4.67%. PV, FV and setback ranged from 193.5-462.8, 123.4-280.9, and 31-59.3 RVU, respectively. PKT and PST ranged from 3.93-4.44 min and 62.7-75.9 °C, respectively. L*, a*, and b* of uncooked starch noodles ranged from 61.6-92.7, 4.9-6.3, and 22.9-32, respectively. Chewiness, hardness, and gumminess ranged from 133.7-299.9, 605.1-958.2, and 302.2-523.4 N, respectively. L*, a*, and b* of cooked starch noodles ranged from 93.2-102.1, 1.07-3.01, and -5.7-21.04, respectively. Chewiness, hardness, and gumminess ranged from 13.5-5.9, 10.0-22.0, and 8.2-18.9 N, respectively. In the preference test of both uncooked and cooked cassava starch noodles, colour, transparency, glossiness, and overall acceptability ranged from 5.4-8.4, 5.3-8.4, 5.3-8.4, and 5.4-8.4, respectively, with noodles made from TMS 01/1206 cassava having the highest overall acceptability value of 8.4 out of the 9 hedonic score. The cassava starches differed significantly in terms of their colour, physicochemical and functional properties. The most acceptable starch noodles were obtained from TMS 01/1206. The acceptability scores of colour and glossiness of the cassava starch noodles were significantly higher than those of the reference noodle sample. It can therefore be concluded that cassava starch has a very high potential in the production of starch noodles.